Social inclusion of persons with disability in employment: what would it take to socially support employed persons with disability in the labor market? - Chumo, Ivy; Kabaria, Caroline; Mberu, Blessing (Frontiers in Rehabilitation Sciences, 2023)
Introduction One of the major challenges that persons with disabilities (PWDs) are facing globally is unemployment. The challenge is attributed to systems that are not built with inclusivity in mind by employers. As such, the work of inclusion is not inviting PWDs to do more but to make a difference through social support. Most research on inclusion in the employment of PWDs in low-income settings has been concentrated upon the labor “supply” side, and to the best of our knowledge, no specific studies moved toward inclusion in employment issues from the employers’ perspective in informal settlements. Notably, our research question is: “what would it take to socially support employed PWD in informal settlements building from the perspectives of employers.” Methods This paper used data from in-depth interviews with 38 service providers in the education, health, water, sanitation, and solid waste management sectors and two sub-county officials in two informal settlements in Nairobi, Kenya. The service providers were employers or entrepreneurs who had hired PWDs in their workspaces and the sub-county officials that had vast experiences with employed PWDs. Data from transcripts were analyzed by the research team using content analysis. Results The social support offered to employed PWDs included listening to them with a concern; identifying their strengths and obstacles; planning for them based on their qualities, knowledge, and experience and linking them with existing opportunities; creating specific opportunities and facilitating their access to opportunities; gradual withdrawal of support by support group; and, lastly, compromise by employers with PWD inclusion strategies. Study participants described how misdirected and inadequate resources, dissatisfaction and unhappiness, and conflicts at the workplace associated with non-inclusion were constraints to social support. Employment matters affecting PWDs are complex and require multi-pronged context-specific social support approaches. Essential to the functioning of an inclusive workplace for PWDs were communication, coordination, sharing of the workload, and supporting individual PWD. Conclusion Inclusion of PWDs in the labor market is about generating a supportive workplace where people are valued and appreciated without judgement for what they can contribute. Notably, in the absence of jobs for everyone and high unemployment rates among every segment of the population, there is a need for an awareness creation, mobilization, and sensitization of employers and investors around the competencies of PWDs and their need to socially support on an impartial basis. On the other hand, employment centers could establish stations in low-income areas to advise and support PWDs on career opportunities that are disability-friendly and partner with employers to avail information about the capabilities of PWDs. Conversely, the government should provide some tax-related benefits to employers to upsurge employer incentives for hiring PWDs and empower employers on benefits and positive culture of employing PWDs. At all times, employers should be hands-on and involve diverse stakeholders to implement current policies and frameworks in different work contexts across the country and beyond.